Isolation and characterization of phosphate solubilizing actinomycetes from soil of agric-fields - A.K. ROY, KISLAY KUMARI* and (Indian Phytopathology, 2016)
The present study was carried out to establish a suitable protocol for the screening of phosphate solubilizing actinomycetes from agricultural fields of Bihar. Altogether 20 isolates with distinct morphology were isolated and characterized from soil of different crop fields and screened on modified starch casein agar (SCA) containing Calcium phosphate as a sole â€œPâ€ source for phosphate solubilizing activity. Out of 20 isolates, 14 showed the activity of phosphate solubilization which were numbered as AKR1 to AKR20. On screening maximum p-solubilizing activity was recorded at pH 7.0 within 10 days of incubation period. Amongst all isolates, AKR14 and AKR18 were found to have maximum activity of phosphate solubilization.